Peculiarities of electron-phonon interaction in Pr³⁺ centers of SrCl₂:Pr single crystals - Antonyak, O.T.; Voloshinovskii, A.S.; Vistovskyy, V.V.; Chornodolskyy, Ya.M. (Functional Materials, 2013)
The luminescence excitation and emission spectra of SrCl₂:Pr single crystals containing 0.2 mol. % Pr were investigated at T=10 K using vacuum ultraviolet synchrotron radiation. From analysis of the fine structure of the low-energy excitation band of an activator, the following main frequencies associated with the local structure of the activator centers were found in the phonon spectrum of SrCl₂:Pr crystal: 194; 210; 266 and 298 cm⁻¹.